Electrically conductive foams via high internal phase emulsions with polypyrrole-modified carbon nanotubes: Morphology, properties, and rheology. (1st March 2022) - Lee, Song Hee; An, Ji Hun; Kim, Yeong Jae; Lee, Seong Jae
Abstract: Electrically conductive polystyrene/carbon nanotube (CNT) microcellular foams were prepared via a high internal phase emulsion (HIPE) polymerization technique. To improve the electrical conductivity of the microcellular foams and the chemical affinity with the oil phase of HIPEs, CNTs were modified with a conductive polymer, polypyrrole (PPy). The dispersibility and performance of the PPy-modified CNTs (PPy-CNTs) in the foams were evaluated by the morphology, electrical conductivity, compression properties, and rheological properties. The dispersion and intrinsic properties of PPy-CNTs with respect to the ultrasonic intensity and time were confirmed by the morphology and electrical conductivity of the foams. As the PPy-CNT content increased, the cell size of the foams decreased, while the electrical conductivity increased. The electrical percolation threshold of PPy-CNT in the microcellular foams was as low as 0.23 wt% (w.r.t. dry foam) owing to the excellent dispersion of CNTs coated with the conductive polymer. The incorporation of PPy-CNTs significantly affected the rheological properties of the emulsions. As the PPy-CNT content increased, the yield stress and storage modulus increased, indicating that the emulsion gradually changed into a solid-like material. The crush strength of the foams increased with the PPy-CNT content and agitation speed. Graphical abstract: Image 1 Highlights: Electrically conductive PS/CNT microcellular foams were prepared via HIPE templates. To improve the conductivity, CNTs were modified with a conductive polymer PPy. As the PPy-CNTs increased, the cell size decreased and the conductivity increased. The electrical percolation threshold of PPy-CNT was 0.23 wt% (based on dry foam).